Jaranan Samboyo Putro Community Communication Strategy in Preserving the Culture of Kurungrejo Village Prambon District Nganjuk Regency - Sinta Kusuma Wardani; Qomarul; Prima (Journal of Communication, Sustainability, and Empowerment, 2025)
The preservation of traditional jaranan arts in Nganjuk Regency, especially the Samboyo Putro jaranan community in Kurungrejo Village, faces the challenges of modernization and globalization that affect the culture and social of the community. This community adapts by combining modern elements and using digital technology to maintain its existence and attract the interest of the younger generation. However, they also experience communication barriers and have to compete with increasingly popular digital entertainment. This study aims to analyze the communication strategy of the Samboyo Putro jaranan community in preserving culture in Kurungrejo Village and identify supporting and inhibiting factors in these preservation efforts. This research uses a qualitative approach with a descriptive approach. Data were obtained through interviews and observations with six informants. The results of this study show that the communication strategy of the Samboyo Putro jaranan community in preserving culture uses ways to recognize communication targets, choose communication media, such as combining traditional and digital media appropriately, assessing the purpose of communication messages, and maximizing the role of credible and empathetic communicators. The supporting factor, the Samboyo Putro jaranan community uses the slogan as a community identity, socialization and education, maintaining traditional pakem, modifying music and creations, community support, community support, community and government support, and the use of social media. Inhibiting factors, the impact of the Covid-19 pandemic, suboptimal management of social media, modernization and globalization challenges, limited resources, competition with modern entertainment, and lack of regeneration.